2002
DOI: 10.2135/cropsci2002.4890
|View full text |Cite
|
Sign up to set email alerts
|

Additive Main Effect and Multiplicative Interaction Analysis of National Turfgrass Performance Trials: I. Interpretation of Genotype × Environment Interaction

Abstract: The additive main effect and multiplicative interaction (AMMI) analysis has been shown to be effective in understanding complex genotype × environment (GE) interactions typical of National Turfgrass Evaluation Program (NTEP) variety trials. Interactions in such complex data sets are difficult to understand with ordinary analysis of variance (ANOVA). NTEP relies on ANOVA procedures (the basis of which is an additive model that does not sub‐partition the interaction) for analysis of turf quality data. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 19 publications
(37 reference statements)
2
92
0
1
Order By: Relevance
“…The definition of the environmental factor contributing to the observed G 9 E interactions empowers the breeder to focus the search for relevant genetic variation for resistance/ tolerance to the defined production constraint, rather than dealing with the amorphous search for specific or broad adaptation. In National Turfgrass trials in the USA, Ebdon and Gauch (2002) observed that leaf spot disease incidence explained a large proportion of observed G x E interactions for quality performance and resulted in narrow adaptation of tested genotypes. Byth et al (1976) attributed a number of strong G 9 E interactions for yield in wheat to the incidence of foliar diseases and the presence of genetic variation for resistance to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of the environmental factor contributing to the observed G 9 E interactions empowers the breeder to focus the search for relevant genetic variation for resistance/ tolerance to the defined production constraint, rather than dealing with the amorphous search for specific or broad adaptation. In National Turfgrass trials in the USA, Ebdon and Gauch (2002) observed that leaf spot disease incidence explained a large proportion of observed G x E interactions for quality performance and resulted in narrow adaptation of tested genotypes. Byth et al (1976) attributed a number of strong G 9 E interactions for yield in wheat to the incidence of foliar diseases and the presence of genetic variation for resistance to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The biplot graph, which clearly displays complex yield patterns (Gauch 1992;Krualee et al 2012), can capture 90% of treatment variation (Krualee et al 2012). Although AMMI model analysis results are based simply on yield statistics (not environmental data), Ebdon and Gauch (2002) have reported that AMMI environmental statistics correlate with environmental factors. An ideal plant variety exhibits both high yields and stability of performance (Eberhart & Russell 1966) over a wide range of environments (Allard & Bradshaw 1964).…”
Section: Ammi Analysismentioning
confidence: 99%
“…In particular, great differences in nodule dry matter among genotypes were associated with differences in seed nitrogen concentration. Furthermore, the targeting of genotypes to specific environments is difficult when GE (genotype × environment) interaction is present since their expression is less predictable and cannot be interpreted based only on G and E means (Ebdon and Gauch 2002;González et al 2006). Crop-breeding programs should also take GE interaction into consideration and estimate its magnitude relative to the magnitude of G and E effects, which affect specific traits.…”
Section: Introductionmentioning
confidence: 99%